The effectiveness of salbutamol nebulizer alone versus salbutamol nebulizer with added atroven in asthmatic patients at emergency department HUSM - Mian, Md Saed (2001)
OBJECTIVE The objective of this study is to compare the effectiveness of nebulized salbutamol alone versus nebulized salbutamol combined with ipratropium bromide (Atrovent®) on asthmatic patients presenting to the emergency department. METHODS The study is a prospective, single blind, randomized clinical trial conducted at the emergency department, University Hospital (Hospital Universiti Sains Malaysia) Kubang Kerian, Kelantan. Patients were included in the study if they fulfilled the inclusion criteria and presented with acute exacerbation of asthma. The patients were divided into two groups, nebulizer salbutamol alone as group 1 and nebulizer salbutamol with Atrovent® as group 2. The dose used was 5 milligrams for salbutamol and 0.5 milligrams for ipratropium bromide (Atrovent®). Patients were selected in either group by identification on presentation at emergency department with numbers, patients who received odd numbers belong to group 1 and even numbers belong to group 2. Nebulization was given by oxygen drive at a flow of 5 - 8 litres per minute and peak expiratory flow rate measurements were recorded at baseline (before nebulizer) and after the first 30 minutes. Other parameters taken for clinical evaluation include heart rate, oxygen saturation, blood pressure and respiratory rate using PropaqTM brand monitor. The data was analysed using SPSS® version 9.0 with statistical significance taken as p value less than 0.05. RESULTS A total of 73 patients aged 13 - 60 years old were selected with the mean (+ SO) of 31.19 (14.81) in group one and (± SO) of 28.93 (13.85) in group two. Of these, 56 patients were included in the study and the remaining 13 patients were excluded as they did not fulfil the criteria. There were 26 patients in group 1 and 30 patients in group 2 of which 30 were male patients and 26 were female patients. Statistically, the distribution of male and female did not show any significant difference. From this study it was found that: 1. Peak expiratory flow rate at baseline in both groups was not statistically different (p value more than 0.05). 2. Both groups study have shown that it improved significantly in peak expiratory flow rate from baseline to the first 30 minutes of therapy with p value less than 0.05, but the peak expiratory flow rate statistically is not significant when the two groups were compared together (p value more than 0.05). 3. No Significant difference in the number of patients that were admitted to ward. 4. No significant difference in the clinical parameter of heart rate. blood pressure, oxygen saturation and respiratory rate statistically. CONCLUSION In this study, the data showed that nebulizer salbutamol alone and nebulizer salbutamol combined with Atrovent® both resulted in bronchodilatation and significant improvements in measured peak expiratory flow rate (p value less than 0.05). However, when these results were compared statistically between the two groups, it was not of statistical significance (p value more than 0.05). The results showed that adding or not adding Atrovent® had no significance in the treatment of acute exacerbation of bronchial asthma in the first 30 minutes of nebulizer therapy.